Medical Assisting: Administrative & Clinical Competencies (Update), 8th Edition - Michelle Blesi (Cengage Learning, 2017)
MEDICAL ASSISTING: ADMINISTRATIVE AND CLINICAL COMPETENCIES UPDATE, Eighth Edition, delivers the critical cognitive (knowledge base), psychomotor (skills) and affective (behaviors) for entry-level medical assistants in an easy-to-understand and proven format. Newly organized for greater effectiveness, the text also includes the latest in Nutrition, the Affordable Care Act (ACA), ICD-10 and updated electronic health records throughout the entire text. In addition, the text highlights have been expanded with personal growth topics like professionalism, teamwork and time management. Updated and innovative, the 8th edition of Medical Assisting: Administrative and Clinical Competencies uses multiple in-text features and exclusive technology products to prepare students for a successful career in medical assisting, and give them a significant advantage in today's competitive marketplace. Additionally, the 8th edition is aligned and mapped to the current ABHES standards and newly approved 2015 CAAHEP standards. The updated printing of the eighth edition includes new ICD-10 coding information, as well as revised and updated coding content.